Kdm6b regulates cartilage development and homeostasis through anabolic metabolism. Issue 7 (17th March 2017) - Dai, Jun; Yu, Dongsheng; Wang, Yafei; Chen, Yishan; Sun, Heng; Zhang, Xiaolei; Zhu, Shouan; Pan, Zongyou; Heng, Boon Chin; Zhang, Shufang; Ouyang, Hongwei
Abstract : Objectives: Epigenetic mechanisms have been reported to play key roles in chondrogenesis and osteoarthritis (OA) development. Here, we sought to identify specific histone demethylases that are involved and delineate the underlying mechanisms. Methods: We screened the expression of 17 distinct histone demethylases by quantitative real time PCR (qRT-PCR) during chondrogenic differentiation of C3H10T1/2 cells. The role of Kdm6b in cartilage development was then analysed with transgenic Col2a1-CreER T2 ;Kdm6b f/f . RNA-Seq was applied to explore the underlying changes in chondrocytes upon knockdown of Kdm6b. Experimental OA in mice was induced by destabilisation of the medial meniscus in C57BL/6J (wild type, Kdm6b f/f and Col2a1-CreER T2 ;Kdm6b f/f ) mice, either with intra-articular injection of shKdm6b lentivirus or after tamoxifen treatment. Mouse joints and human cartilage samples were used for histological analysis. Results: Kdm6b expression was significantly increased during cartilage development. Col2a1-CreER T2 ;Kdm6b f/f mice displayed obvious skeletal abnormalities at E16.5 and E18.5 with intraperitoneal injection of tamoxifen at E12.5. RNA-Seq and qRT-PCR analyses revealed decreased expression of chondrocyte anabolic genes in Col2a1-CreER T2 ;Kdm6b f/f chondrocytes. The histological OA score was significantly higher in mice injected with Kdm6b short hairpin RNA lentivirus. Col2a1-CreER T2 ;Kdm6b f/f mice exhibited accelerated OA development at 8 and 12 weeks following surgical induction. The number of Kdm6b-positive chondrocytes was lower in both mice and human OA cartilage samples. Conclusions: These findings indicate that knockdown of Kdm6b in chondrocytes leads to abnormal cartilage development and accelerated OA progression via inhibition of the anabolic metabolism of chondrocytes. Understanding the epigenetic mechanism of joint cartilage development and homeostasis would be useful for development of new therapeutic modalities for OA.